Helicobacterpylori Gastritis Presenting as an Umbilicated Polypoidal Lesion - Deshidi, Srinu; Mahajan, Gaurav; Appasani, Sreekanth (Journal of Gastrointestinal Infections, 2025)
Dyspepsia is characterized by chronic or recurrent pain in the upper abdomen and is the most common indication for upper gastrointestinal endoscopy. One-third of dyspeptic patients in India have Helicobacter pylori infection. Endoscopic findings suggestive of H. pylori infection include mucosal atrophy, diffuse redness, spotty redness, mucosal swelling, ulcerations, and nodularity. Lymphoid hyperplasia of the stomach is a benign and nonspecific condition that occurs due to chronic H. pylori infection and is characterized histologically by an increase in the size and number of lymphoid follicles. It appears endoscopically as a nodule or rarely as an umbilicated polypoid lesion. We report a case of dyspepsia who presented with epigastric pain and post-prandial abdominal fullness that did not respond to proton-pump inhibitors and underwent gastroscopy, which revealed an umbilicated polypoidal lesion in the antrum, which turned out to be H. pylori-associated chronic active gastritis.
Keywords: dyspepsia; gastritis; Helicobacter pylori; umbilicated nodule